(untitled) (European Journal of Behavioral Sciences, 2025)
Neuroarchitecture is the interdisciplinary field standing at the crossroads of neuroscience and architecture that investigates how the built environment interfaces with human neural mechanisms to shape behavior, emotion, and cognition. While highly researched in application to healthcare and educational settings, how neuroarchitecture might conceptually shape and reframe the social sciences remains under consideration. The theoretical and empirical points of intersection, for instance, between neuroarchitecture and social sciences, have been made relevant within the framework of understanding human behavior, social interaction, and well-being in the built environment. Using a multidisciplinary perspective, this study outlines a conceptual framework for how neuroarchitectural insights can be integrated into the methodologies of social sciences. The approach integrates neuroscience, architecture, and environmental psychology through a comprehensive review of empirical and theoretical research on the topic. Major themes have been identified through bibliometric analysis and co-occurrence mapping to trace the evolution of neuroarchitecture and its relevance to social science contexts. Further, case studies in urban design and policy-making were investigated to point out practical applications, giving a base for actionable strategies that address social challenges through human-centered environmental design. The present study opens new perspectives for research into the way the built environment influences individual and collective experience and, on its part, allows novel insights into urgent problems in social sciences. Furthermore, it brings together different viewpoints regarding practical applications of neuroarchitecture to urban planning, policy decisions, and community development as a means of creating supportive environments that respond to diverse human needs. The study underlines the fact that the solution to some key challenges requires the collaboration of neuroscientists, architects, and social scientists. Hence, the study attempts to further both disciplines by offering bridges between the fields of neuroscience and social science.